A spider’s vibration landscape: adaptations to promote vibrational information transfer in orb webs - Mortimer, B (Oxford University Press, 2019)
Spider orb webs are used not only for catching prey, but also for transmitting vibrational information to the spider. Vibrational information propagates from biological sources, such as potential prey or mates, but also abiotic sources, such as wind. Like other animals, the spider must cope with physical constraints acting on the propagation of vibrational information along surfaces and through materials—including loss of energy, distortion, and filtering. The spider mitigates these physical constraints by making its orb web from up to five different types of silks, closely controlling silk use and properties during web building. In particular, control of web geometry, silk tension, and silk stiffness allows spiders to adjust how vibrations spread throughout the web, as well as their amplitude and speed of propagation, which directly influences energy loss, distortion, and filtering. Turning to how spiders use this information, spiders use lyriform organs distributed across their eight legs as vibration sensors. Spiders can adjust coupling to the silk fibers and use posture to modify vibrational information as it moves from the web to the sensors. Spiders do not sense all vibrations equally—they are least sensitive to low frequencies (<30 Hz) and most sensitive to high frequencies (ca. 1 kHz). This sensitivity pattern cannot be explained purely by the frequency range of biological inputs. The role of physical and evolutionary constraints is discussed to explain spider vibration sensitivity and a role of vibration sensors to detect objects on the web as a form of echolocation is also discussed.